Recent Advances in the Synthesis and Biomedical Applications of Heterocyclic NO-Donors - Leonid L. Fershtat; Egor S. Zhilin (Molecules, 2021)
Nitric oxide (NO) is a key signaling molecule that acts in various physiological processes such as cellular metabolism, vasodilation and transmission of nerve impulses. A wide number of vascular diseases as well as various immune and neurodegenerative disorders were found to be directly associated with a disruption of NO production in living organisms. These issues justify a constant search of novel NO-donors with improved pharmacokinetic profiles and prolonged action. In a series of known structural classes capable of NO release, heterocyclic NO-donors are of special importance due to their increased hydrolytic stability and low toxicity. It is no wonder that synthetic and biochemical investigations of heterocyclic NO-donors have emerged significantly in recent years. In this review, we summarized recent advances in the synthesis, reactivity and biomedical applications of promising heterocyclic NO-donors (furoxans, sydnone imines, pyridazine dioxides, azasydnones). The synthetic potential of each heterocyclic system along with biochemical mechanisms of action are emphasized.